"It's a Black Hole . . .": Exploring Teachers' Narratives and Practices for Digital Literacies in the Adult EAL Context. Issue 3 (August 2021) - Tour, Ekaterina; Creely, Edwin; Waterhouse, Peter
A strength-based approach to teaching digital literacies can advance language education for adults from refugee and migrant backgrounds, preparing them for life in a new country. This article draws on a 6-month ethnographic study at an adult English language center in Australia and explores teachers' perspectives and practices related to teaching digital literacies to understand how prepared they are to employ learners' own resources. Using sociomaterial theory, this research found that English as an Additional Language (EAL) teachers' narratives about learners focused on what they lacked rather than what they brought to learning. It also found that while teaching practices utilized some strength-based pedagogical principles, the teachers viewed their work as being deficient. They did not always recognize their agential power nor did they overtly understand that the technology itself afforded this power. The article concludes with implications for EAL practice and professional learning of teachers who work in the adult sector.